A Distinctive Architectural Example from the Era of Ottoman Westernization. Palazzo Corpi; The Former American Embassy Building - Alev Erarslan (Architecture Image Studies Scientific Journal)
Ottoman architecture begin to change around the beginning of the 18th century. The main factors influencing this change were the opening out to the West of Ottoman culture, relations with the West, and the inclusion of western architects in Ottoman society. The new look that classic Ottoman architecture assumed was to evolve under the thematic influence of European architects. Modifications were manifested not only in civil architecture but even in religious structures, which represented the breaking point of tradition. One of the cultural dynamics that represented the driving force of the changes in Ottoman architecture in the 18th century, producing innovatively novel effects under the European influence, was the various imported styles. The influence of Western art continued to make a mark on Ottoman architecture as from the start of the 18th century up until the end of the 19th century. The Edict of Reform (Tanzimat Fermanı) proclaimed in 1839 added momentum to the westernization movement, bringing with it new cultural dynamics and new types of structures as a result of the changing social clime. One of these architectural types was represented by buildings that housed diplomatic missions. The aim of this article is to examine the architectural and decorative characteristics of one of the important representations of the type of embassy architecture prevailing in the era of Ottoman westernization–the former American Embassy building in Istanbul, originally called the “Palazzo Corpi.” Toward this purpose, we will introduce in detail the plan and spatial organization of the building, the features of its mass, facades and interior.